2019
DOI: 10.1108/ijqrm-07-2018-0193
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma for the healthcare sector: a multiple case study analysis from the Indian context

Abstract: Purpose The purpose of this paper is to explore the voice of the customer, key performance indicators, critical to quality characteristics, critical success factors, and commonly used tools and techniques for deploying the Lean Six Sigma (LSS) strategy in Indian private hospitals, with special attention to the medical records. Design/methodology/approach The study utilizes the action research methodology to obtain a greater understanding of the use of LSS in the Indian healthcare sector. Multiple case studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(124 citation statements)
references
References 64 publications
3
119
0
2
Order By: Relevance
“…Thus, it ensures the active participation of the members from the organization under study. This exploratory nature assists not only to develop a case study but also to determine the answers to the RQs with more insight (Coughlan and Coghlan, 2002;Bhat et al, 2019). Moreover, it is one of the better methodologies in operations management research to tap the potential of the practitioners and academicians' TQM 33,2 Particulars LSS Principle 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it ensures the active participation of the members from the organization under study. This exploratory nature assists not only to develop a case study but also to determine the answers to the RQs with more insight (Coughlan and Coghlan, 2002;Bhat et al, 2019). Moreover, it is one of the better methodologies in operations management research to tap the potential of the practitioners and academicians' TQM 33,2 Particulars LSS Principle 1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, most of the LSS researches are empirical in nature, which demands real-world/ primary data and subsequently, this data assists in developing the case study. Since, quality problems in the manufacturing context are usually treated as a case in terms of documentation and analysis, AR is the better and dominant approach for LSS to unearth the answers to RQs and ensure organizational change (Aboelmaged, 2010;Bhat et al, 2019). The researchers, being Master Black Belt (MBB) in Six Sigma, assisted the industry in validating the potential causes and deployment of solutions to enhance the system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined LSS strategy integrates human aspects (such as leadership, customer focus and cultural change) and process aspects (such as process capability, process management and statistical thinking) for continuous improvement (Bhat et al, 2019;Antony, 2011). Integrating Lean principles of reducing waste with Six sigma's aim of reducing variation through value stream mapping and analysis and statistical process control can serve to improve patient satisfaction and outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The present work provides impetus for system wide application of JIT with through and contextual understanding among the different JIT enablers. According to a study conducted by Hussein and Zayed (2020) (Bhat et al, 2019;Vaishnavi and Suresh, 2020;Kaswan and Rathi, 2021). Naidoo and Fields (2019) also found that strategic leadership and organizational attitude and integration of Lean practices as key factors for successful deployment of Lean thinking in healthcare.…”
Section: Sensitivity Analysismentioning
confidence: 99%